An Energy-Heterogeneous Clustering Scheme to Avoid Energy Holes in Wireless Sensor Networks - Gong Bencan; Jiang Tingyao; Xu Shouzhi; Chen Peng (International Journal of Distributed Sensor Networks)
Clustering techniques can reduce energy consumption of nodes and increase the scalability of the network. However, in uniformly deployed clustering wireless sensor networks, the uneven distribution of communication loads often causes the energy-hole problem, which means that the energy of the nodes in the hole region will be used up sooner than the nodes in other regions. In order to solve the problem, this paper theoretically analyzes the energy consumption of nodes in different network areas, gives the expression of the optimal energy distribution of heterogeneous nodes, and designs an energy-efficient clustering routing protocol. The goal of our work is to propose an energy-heterogeneous clustering scheme (EHCS) that allows the initial energy of the sensor nodes to be varied with the distance to sink. The nearer nodes from sink have more energy. Simulation results show that the method can balance the energy consumption among sensor nodes, achieve an obvious improvement on the network lifetime, and effectively avoid the energy-hole problem.